Experimental and numerical investigations of bi-injection moulding of PA66/LSR peel test specimens. (October 2020) - Sahli, M.; Barrière, T.; Roizard, X.
Abstract: Bi-injection moulding is a widely used process to manufacture engineering products and consumer goods. Typically, a thermoplastic is combined with rubber or another thermoplastic to create colour differences or hard and soft areas, respectively. The aim of this study was to optimise the injection parameters and processing conditions for the moulding of two-component standard peel test specimens with suitable functional properties. In this work, all parameters of thermo-rheo-kinetic behaviour were identified to predict the entire filling stage and the effect of a liquid silicone rubber cross-linking reaction during the injection moulding process. The models of Carreau-Yasuda and Isayev-Deng regarding the thermal dependence assumed by Arrhenius' law were used. In our study, over-injection moulding is simulated and examined using finite element software (Cadmould 3D) to investigate the thermo-rheo-kinetic behaviour and the adhesion of liquid silicone rubber during the filling mould process in over-moulding. Numerical simulation results were then compared with the experimental results, and good agreement was obtained. Graphical abstract: Image 1 Highlights: Carreau-Yasuda/Isayev-Deng models well reproduce the rheological behavior and the cross-linking reaction of rubber materials. Over-moulding numerical models investigated to determines the influence of factors process/material on the adhesion quality. The difference in thermal conductivity between the PA6 and the mould condacted an accelerated the vulcanisation kinetics. The mould filling depended on process/material data input for injection moulding process of rubber bi-compound.